KEPEMIMPINAN KEPALA SEKOLAH DALAM MENGELOLA SATUAN PENDIDIKAN DENGAN KARAKTERISTIK PENDANAAN YANG BERBEDA : STUDY KASUS DI SEKOLAH DASAR - Munadliroh; Edi Kurniawan, Edi Kurniawan; Nanik Wijayati; Decky Avrilianda (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze principal leadership practices in managing two primary schools with distinct funding characteristics. A qualitative multi-case study design was employed, with data gathered through in-depth interviews, participant observation, and document analysis of school budget plans and financial reports. Data were synthesized using Miles, Huberman, and Saldaña's interactive model. Findings reveal that funding differentiation significantly shapes contextual and adaptive leadership practices through three primary strategies: fiscal-based program calibration, justice framing in organizational communication, and relational buffering through collective participation. These strategies allow principals to navigate financial constraints while maintaining institutional goals. As a theoretical contribution, the study proposes the concept of contextual fiscal leadership to the field of school leadership studies within tiered funding systems. This concept emphasizes the necessity for school leaders to harmonize pedagogical visions with fiscal realities to ensure organizational resilience.